Development of Web-Based Orcakes Patisserie Online Ordering and Class Registration System - Radzin, Puteri Nur Fathimah; Hamid Ali, Firkhan Ali (Applied Information Technology And Computer Science, 2026)
The Orcakes Patisserie Online Ordering and Class Registration System is a complete web-based platform developed to streamline order management and class registration processes. To guarantee flexibility and efficiency, the system uses an object-oriented approach to divide its essential functions—secure order placing, payment processing, real-time class registration, and product browsing—into modular and reusable components. The development approach uses a prototyping model to continually align with user expectations and UML diagrams to represent system activities. Robust organizing of data is achieved with MySQL, which supports features like a comprehensive product catalog, user authentication, real-time alerts, and an easy-to-use admin interface for scheduling classes, managing inventory, and communicating with clients. The platform simplifies administrative duties, improves the client experience, and lowers mistakes by centralizing operations. Its safe and scalable architecture assures long-term dependability and usability, meeting Orcakes Patisserie's changing requirements while providing a smooth and effective user experience for both administrators and clients.